(untitled) - Lana, Nerina Belén; Fontana, Ariel Ramón; Ciocco, Nestor Fernando; Altamirano, Jorgelina Cecilia (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Determination of polybrominated diphenyl ethers in water samples from Mendoza River Basin by HS-SPME-GC-MS/MS (2010)

(untitled)
Polybrominated diphenyl ethers (PBDEs) are considered persistent organic pollutants because of their ubiquity, persistence and bioaccumulation. Its harmful effects on human health and the environment, has led to its inclusion of the Stockholm Convention. Little information is found about PBDEs in abiotic systems of the South America in open literature. This paper reports the presence and concentration level of four PBDEs congeners in Mendoza River, Argentina. The selected PBDEs were: 2,2',4,4'-tetrabromodiphenyl ether (BDE-47), 2,2',4,4',5-pentabromodiphenyl ether (BDE-99), 2,2',4,4',6-pentabromodiphenyl ether (BDE- 100) and 2,2',4,4',5,5'-hexabromodiphenyl ether (BDE-153). The analytical methodology used was head space-solid phase micro extraction combined with gas chromatographymass spectrometry (HS-SPME-GC-MS/MS). Several variables, including pH, salting out, extraction technique type and extraction time were studied and optimized over the relative response the target analytes. The precision of HS-SPME-GC-MS/MS evaluated over five replicate, leading RSDs values <13%, detection limits (S/N=3) ranging from 0.03 pg ml-1 to 0.12 pg ml-1 and the calibration graph was linear with r2=0.9959. BDE-47 and BDE-100 were the predominant congeners found in the analyzed samples. Their concentrations ranged from not detected to 1.9 pg ml-1 and to 0.5 pg ml-1, respectively.